Long Non-coding RNA FER1L4 Mediates the Autophagy of Periodontal Ligament Stem Cells Under Orthodontic Compressive Force via AKT/FOXO3 Pathway - Huang, Yiping; Liu, Hao; Guo, Runzhi; Han, Yineng; Yang, Yuhui; Zhao, Yi; Zheng, Yunfei; Jia, Lingfei; Li, Weiran (Frontiers in Cell and Developmental Biology, 2021)
Orthodontic tooth movement is achieved by periodontal tissue remodeling triggered by mechanical force. It is essential to investigate the reaction of periodontal ligament stem cells (PDLSCs) for improving orthodontic therapeutic approaches. Autophagy is an endogenous defense mechanism to prevent mechanical damage of environmental change. Long non-coding RNAs (lncRNAs) are key regulators in gene regulation, but their roles are still largely uncharacterized in the reaction of PDLSCs during orthodontic tooth movement. In this study, we showed that autophagy was significantly induced in PDLSCs under compressive force, as revealed by the markers of autophagy, microtubulerassociated protein lightchain 3 (LC3) II/I and Beclin1, and the formation of autophagosomes. After the application of compressive force, lncRNA FER1L4 was strongly upregulated. Overexpression of FER1L4 increased the formation of autophagosome and autolysosomes in PDLSCs, while knockdown of FER1L4 reversed the autophagic activity induced by mechanical force. In mechanism, FER1L4 inhibited the phosphorylation of protein kinase B (AKT) and subsequently increased the nuclear translocation of forkhead box O3 (FOXO3), and thus mediated autophagic cascades under compressive strain. In mouse model, the expression of Lc3 as well as Fer1l4 was increased in the pressure side of periodontal ligament during tooth movement. These findings suggest a novel mechanism of autophagy regulation by lncRNA during periodontal tissue remodeling of orthodontic treatment.